DESIGN OF INFORMATION SYSTEM FOR INDUSTRIAL INTERNSHIP MANAGEMENT IN INFORMATICS ¬EDUCATION PROGRAM - Aknul, Azizi Azwir; Alfiriani, Adlia; Pernanda, Angry Yulio (Universitas PGRI Sumatera Barat, 2024)
This study aims to develop an efficient internship management information system for the Informatics Education Program at University PGRI Sumatera Barat. Currently, the management of internship programs in the industry is still manual, time-consuming, and accessing old information is challenging due to paper-based files. The proposed information system will assist students and internship program administrators in managing industrial internships. It involves several users, such as administrators, students, internship supervisors, and industry mentors, each with limited access based on their respective roles. Students can fill out internship registration forms, request supervisors, and upload daily and final internship reports. Internship supervisors and industry mentors can validate students' logbooks and reports and provide final internship grades. Functional system requirements include login features and dashboards for each user. Access to the system is through computer devices using software like XAMPP, Visual Studio Code, and Chrome. The system is expected to enhance the efficiency of the internship program and provide valuable benefits for future internship management. The System Development Life Cycle (SDLC) with the waterfall model is employed as the method for system development, covering stages such as planning, analysis, design, implementation, testing, and maintenance.